2012
DOI: 10.1037/a0029737
|View full text |Cite
|
Sign up to set email alerts
|

From documenting to eliminating disparities in mental health care for Latinos.

Abstract: The U.S. Surgeon General's report Mental Health: Culture, Race and Ethnicity--A Supplement to Mental Health: A Report of the Surgeon General (U.S. Department of Health and Human Services, 2001) identified significant disparities in mental health care for Latinos and recommended directions for future research and mental health services. We update that report by reviewing five groundbreaking research projects on the mental health of Latinos that were published since 2001. National studies of adults and children,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 80 publications
(85 reference statements)
2
75
0
Order By: Relevance
“…This recommendation is consistent with the finding that a large portion of Latinos in the general population have reported that they first sought help from a primary care physician for a mental health problem (e.g., Vega et al, 1999). Accordingly, the integration of mental health care with primary health care has been identified as one of the priorities in Latino mental health in the U.S.A (López et al, 2012).…”
Section: Use Of Inter-sectorial Initiativessupporting
confidence: 61%
See 3 more Smart Citations
“…This recommendation is consistent with the finding that a large portion of Latinos in the general population have reported that they first sought help from a primary care physician for a mental health problem (e.g., Vega et al, 1999). Accordingly, the integration of mental health care with primary health care has been identified as one of the priorities in Latino mental health in the U.S.A (López et al, 2012).…”
Section: Use Of Inter-sectorial Initiativessupporting
confidence: 61%
“…For example, large-scale epidemiological studies have revealed that immigrant Latinos in the U.S.A. have a lower prevalence of mental health problems than Latinos born in the U.S.A., that is, second and later generation Latinos (Alegría et al, 2008;López, Barrio, Kopelowicz, & Vega 2012;Vega et al, 1998). In other words, the rates of mental health problems of immigrants are lower than average than those of the general population.…”
Section: Epidemiological Surveillance Needs Assessments and Empiricallmentioning
confidence: 94%
See 2 more Smart Citations
“…18 Educational outreach in the general population, publicizing the benefits of counseling and countering perceived risks, has increased willingness to seek help. 16,19 To date few studies have assessed whether educational campaigns lead to changes in physicians' attitudes and Intervention A resident wellness program (RWP) was designed to lower known barriers limiting resident access to services.…”
Section: Introductionmentioning
confidence: 99%